Biocatalytic methylation and demethylation via a shuttle catalysis concept involving corrinoid proteins. Issue 1 (December 2018) - Farnberger, Judith; Richter, Nina; Hiebler, Katharina; Bierbaumer, Sarah; Pickl, Mathias; Skibar, Wolfgang; Zepeck, Ferdinand; Kroutil, Wolfgang
Abstract Synthetically established methods for methylation of phenols and demethylation of methyl phenyl ethers rely in general on hazardous reagents or/and harsh reaction conditions and are irreversible. Consequently, alternative regioselective methods for the reversible formation and breakage of C-O-ether bonds to be performed under mild and sustainable conditions are highly desired. Here we present a biocatalytic shuttle concept making use of corrinoid-dependent methyl transferases from anaerobic bacteria. The two-component enzymatic system consists of a corrinoid protein carrying the cofactor and acting as methyl group shuttle, and a methyltransferase catalyzing both methylation and demethylation in a reversible fashion. Various phenyl methyl ethers are successfully demethylated and serve in addition as sustainable methylating agents for the functionalization of various substituted catechols. Therefore, this methyl transfer approach represents a promising alternative to common chemical protocols and a valuable add-on for the toolbox of available biocatalysts. Regioselective methods for the reversible formation and breakage of C-O-ether bonds under mild conditions are desired. Here, the authors present a biocatalytic shuttle concept using corrinoid-dependent methyl transferases for demethylating various phenyl methyl ethers and functionalizing substituted catechols.